2019
DOI: 10.1111/jocn.14799
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experience with heart failure treatment and self‐care—A qualitative study exploring the burden of treatment

Abstract: Aims and objectives To explore chronic heart failure patients’ perceptions of the burden related to treatment and self‐care. Background Living with chronic heart failure entails following a demanding treatment regimen, with daily self‐care, which could make patients vulnerable to experiencing treatment burden. Burden of treatment is defined as the “work” the healthcare system passes on to the patients with respect to self‐care at home, and the impact this has on well‐being and quality of life. However, the bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 39 publications
4
42
0
1
Order By: Relevance
“…However, previous studies have reported low adherence rates in self-care behaviors, due to the complexity of self-care and lifelong requirement of medical treatment [9,10]. Thus, many studies have evaluated various types of interventions to improve HF self-care behaviors and associated outcomes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have reported low adherence rates in self-care behaviors, due to the complexity of self-care and lifelong requirement of medical treatment [9,10]. Thus, many studies have evaluated various types of interventions to improve HF self-care behaviors and associated outcomes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Burdens related to treatment and self‐care in HF have been characterized in prior research as overwhelming, difficult work; and adherence to HF self‐care and treatment regimens has been reported to be low (Gallacher et al, ; Mlynarska et al, ; Riegel et al, ). Despite patients' knowledge of self‐care tasks, the burden of the illness and treatment generates problems in maintaining self‐efficacy, which is a personal attribute that changes over time by learning from attempts to manage the HF condition (Nordfonn, Morken, Bru, & Husebø, ; Riegel et al, ; Spaling, Currie, Strachan, Harkness, & Clark, ). None of the aforementioned notions fully captures the capacity term in the HF context.…”
Section: Introductionmentioning
confidence: 99%
“…In the qualitative studies, patients reported that the demands to adhering the complex treatment regimens are onerous and difficult to meet. Some patients also reported troubles on learning new medications and dealing with the burden of medication side effects [32,33].…”
Section: Medication Managementmentioning
confidence: 99%